PERSEPSI KOMUNITAS PEMUDA TANI TERHADAP UPAYA KONSERVASI SUMBER DAYA AIR DI WILAYAH DAS CISADANE HULU DESA PASIR BUNCIR KECAMATAN CARINGIN KABUPATEN BOGOR - Putri Diah Pandan Arum; Suminah Suminah; Bekti Wahyu Utami (AGRITEXTS: Journal of Agricultural Extension, 2018)
This study examines internal and external factors of youth farmers community perception, examines the perception of youth community towards conservation of water resources, and to analyse the influence between the internal and external factors of the youth farmers community and the perception of the youth farmers  community  towards  the  conservation  of  water  resources.  The  research location was chosen purposely in Pasir Buncir Village, Caringin Sub-district, Bogor Regency which is a village located in the Upper Cisadane River Basin of   Penggerak Cisadane Hulu dan Lingkungan Hidup (PACING community center). Census sampling is34 members of PACING community. This research use multiple linear regression as an anlysis tools. The results showed that: (1) factors affecting perceptions such as non formal  education  are  high,  revenue  is  very  low,  experience  is  high,  government agencies that play a role in socialization and assistance are Badan Pengelola DAS (BPDAS) and Dinas Kehutanan, four government agencies play a role in supervision , opinion leader is considered influential but passive, the existence of privatization is quite bad, and organizational culture is very good in mission implementation, consistency and member involvement, while adaptability is just good (2) perception of member of PACING community toward conservation effort is good, (3) factors that can influence  perception  of  youth  community  significantly  only  non  formal  education factor, experience and organization culture, while other factors such as revenue, government role, opinion leader, impact of privatization, has no significant effect.